Cone beam computed tomography based sex estimation by volume of odontoid process of the second cervical Vertebra - Costa, Andre Luiz Ferreira; Barbieri, Ana Amelia [UNESP]; Gonçalves, Bianca Costa; Silva, Camila Felisbino [UNESP]; Ogawa, Celso Massahiro; Cardoso, Cristiane De Almeida Baldini; Fardim, Karolina Aparecida Castilho; Lopes, Sérgio Lucio Pereira De Castro (Editora Cubo, 2021)
Objective: The aim of this study was to evaluate whether the volume of odontoid process of the second cervical vertebra on CBCT images can be used for sex estimation. Material and Methods: The volume of odontoid process on CBCT images of 138 subjects was measured. In addition, the patients were classified into five age groups. The comparisons between the groups in relation to sex and age were performed by using Mann-Whitney’s test and Kruskal-Wallis’ test, respectively. The ROC curve was used to assess the sensitivity and specificity of the volume to determine the sex. Results: No statistically significant difference was observed between age and volume. Males had significantly larger volumes than females. Values of volume equal to or greater than 1.254 mm3 have sensitivity of 68.2% and specificity of 68.1% to determine male sex. Conclusion: The volume of the odontoid process tends to be larger in males than in females and can be used as sex estimation.
Estimativa sexual baseada em tomografia computadorizada de feixe cônico pelo volume do processo odontóide da segunda vértebra cervical
Keywords: Computer-assisted; Cone beam computed tomography; Diagnostic imaging; Image processing; Sex determination processes